Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
x2 - 5x - 36 = 0
=> x2 - 9x + 4x - 36 = 0
=> x(x - 9) + 4(x - 7) = 0
=> (x + 4)(x - 7) = 0
=> \(\orbr{\begin{cases}x+4=0\\x-7=0\end{cases}}\)
=> \(\orbr{\begin{cases}x=-4\\x=7\end{cases}}\)
6x2 - (2x + 5)(3x - 2) = -12
=> 6x2 - 6x2 + 4x - 15x + 10 = -12
=> -11x = -22
=> x = 2
x2 - 25 = 6x - 9
=> x2 - 25 - 6x + 9 = 0
=> x2 - 6x - 16 = 0
=> x2 - 8x + 2x - 16 = 0
=> x(x - 8) + 2(x - 8) = 0
=> (x + 2)(x - 8) = 0
=> \(\orbr{\begin{cases}x+2=0\\x-8=0\end{cases}}\)
=> \(\orbr{\begin{cases}x=-2\\x=8\end{cases}}\)
1) (x - 2)2 - (x - 3)(x + 3) = 17
=> x2 - 4x + 4 - x2 + 9 = 17
=> -4x = 17 - 13
=> -4x = 4
=> x = -1
2) TTT
3) x2 + 6x - 147 = 0
=> x2 + 19x - 13x - 147 = 0
=> x(x + 19) - 13(x + 19) = 0
=> (x - 13)(x + 19) = 0
=> \(\orbr{\begin{cases}x-13=0\\x+19=0\end{cases}}\)
=> \(\orbr{\begin{cases}x=13\\x=-19\end{cases}}\)
4) (3x - 5)(2x + 3) - 6x2 = 7
=> 6x2 + 9x - 10x - 15 - 6x2 = 7
=> -x - 15 = 7
=> -x = 7 + 15
=> -x = 22
=> x = -22
5) TL
a) \(x^2+2xy+y^2+x+y-2\le0\)
\(\Leftrightarrow\)\(\left(x+y\right)^2+x+y-2\le0\)
\(\Leftrightarrow\)\(\left(x+y+\frac{1}{2}\right)^2\le\frac{9}{4}\)
\(\Leftrightarrow\)\(-2\le x+y\le1\)
b) \(x^2+2y^2+2xy-16y-6x+30=0\)
\(\Leftrightarrow\)\(\left(x^2+2xy+y^2\right)-6\left(x+y\right)=-y^2+10y-30\)
\(\Leftrightarrow\)\(\left(x+y\right)^2-6\left(x+y\right)=-\left(y^2-10y+25\right)-5\)
\(\Leftrightarrow\)\(\left(x+y-3\right)^2=-\left(y-5\right)^2+4\le4\)
\(\Leftrightarrow\)\(1\le x+y\le5\)
1) (x-4)2-36=0
⇔ (x-4)2=36=62
⇔\(\left\{{}\begin{matrix}x-4=6\Rightarrow x=10\\x-4=-6\Rightarrow x=2\end{matrix}\right.\)
2) (x+8)2 = 121 = 112
⇔ \(\left\{{}\begin{matrix}x+8=11\Rightarrow x=3\\x+8=-11\Rightarrow x=-19\end{matrix}\right.\)
3) x2 + 8x + 16 = 0
⇔ (x+4)2=0
⇔ x+4 = 0 ⇒ x = -4
\(\left(x^2+x\right)^2+4\left(x^2+x\right)=12\)
Đặt \(a=x^2+x\)
\(\Leftrightarrow a^2+4a=12\)
\(\Leftrightarrow a^2+4a-12=0\)
\(\Leftrightarrow a^2+6a-2a-12=0\)
\(\Leftrightarrow a\left(a+6\right)-2\left(a+6\right)=0\)
\(\Leftrightarrow\left(a+6\right)\left(a-2\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}a=-6\\a=2\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x^2+x=-6\\x^2+x=2\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x^2+2\cdot x\cdot\frac{1}{2}+\frac{1}{4}+\frac{23}{4}=0\\x^2+2x-x-2=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}\left(x+\frac{1}{2}\right)^2=\frac{-23}{4}\left(loai\right)\\\left(x+2\right)\left(x-1\right)=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=-2\\x=1\end{cases}}\)
Vậy....
a)
DK:tồn tại P \(\hept{\begin{cases}x\ne0\\x\ne-+6\\x\ne3\end{cases}}\)
\(P=\left(\frac{x}{\left(x-6\right)\left(x+6\right)}-\frac{x-6}{x\left(x+6\right)}\right).\frac{x\left(x+6\right)}{2\left(x-3\right)}\\ \)
\(P=\left(\frac{x^2-\left(x-6\right)\left(x-6\right)}{x\left(x-6\right)\left(x+6\right)}\right).\frac{x\left(x+6\right)}{2\left(x-3\right)}\)
\(P=\left(\frac{x^2-\left(x^2-12x+36\right)}{x\left(x-6\right)\left(x+6\right)}\right).\frac{x\left(x+6\right)}{2\left(x-3\right)}\)
\(P=\left(\frac{12\left(x-3\right)}{x\left(x-6\right)\left(x+6\right)}\right).\frac{x\left(x+6\right)}{2\left(x-3\right)}=\frac{6}{x-6}\)
b)6/(x-6)=1=> x-6=6=> x=12
c)x-6<0=> x<6
x là 6 nhé bạn bởi vì 6x6-36=0=36-36=0